Top-down influence on visually induced self-motion perception (vection) - Riecke, B. E.; Schulte-Pelkum, J.; Avraamides, M. N; Heyde, M. von der; Bülthoff, Heinrich H (7. Tübingen Perception Conference (TWK), 2004)
INTRODUCTION: The prevailing notion of visually induced illusory self-motion perception (vection) is that the illusion arises from bottom-up perceptual processes. Therefore, past research has focused primarily on examining how physical parameters of the visual stimulus (contrast, number of vertical edges etc.) affect vection. In this study, we examined the influence of a top-down process: Spatial presence in the simulated scene. Spatial presence was manipulated by presenting either a photorealistic image of the Tübingen market place or modified versions of the same stimulus. Modified stimuli were created by either slicing the original image horizontally and randomly reassembling it or by scrambling image parts in a mosaic-like manner. We expected scene modification to decrease spatial presence and thus impair vection. METHODS: Ten naive observers viewed stimuli projected onto a curved projection screen subtending a field of view (FOV) of 54x40.5$^°$. We measured vection onset times and had participants rate the convincingness of the self-motion illusion for each trial using a 0-100% scale. In addition, we assessed spatial presence using standard presence questionnaires. RESULTS: As expected, scene modification led to both reduced presence scores and impaired vection: Modified stimuli yielded longer vection onset times and lower convincingness ratings than the intact market scene (t(9)=-2.36, p=.043 and t(9)=3.39, p=.008, resp.). It should be pointed out that the scrambled conditions had additional high contrast edges (compared to the sliced or intact stimulus). Previous research has shown that adding vertical high contrast edges facilitate vection. Therefore, one would predict that the scrambled stimuli should improve vection. The results show, however, a tendency towards reduced vection for the scrambled vs. sliced or intact stimuli. This suggests that the low-level information (more contrast edges in the scrambled stimulus) were dominated by high level information (consistent reference frame for the intact market scene). Interestingly, the number of slices or mosaics (2, 8, or 32 per 45$^°$ FOV) had no clear influence on either perceived vection or presence; two slices were already enough to impair scene presence. CONCLUSIONS: These results suggest that there might be a direct relation between spatial presence and self-motion perception. We posit that stimuli depicting naturalistic scenes provide observers with a convincing reference frame for the simulated environment which enables them to feel "spatially present" in that scene. This, in turn, facilitates the self-motion illusion. This work not only can shed some light on ego-motion perception, but also has important implications for motion simulator design and application. SUPPORT: EU grant POEMS-IST-2001-39223 (see www.poems-project.info) and Max Planck Society.
Keywords: Riecke; Riecke_2004; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; talkWithoutPaper; vection